Supported nano-gold catalysts for epoxidation of styrene and oxidation of benzyl alcohol to benzaldehyde - Choudhary, Vasant R.; Dumbre, Deepa K. (Topics in Catalysis, 2009)
Nano-gold particles supported on different alkaline earth oxides (viz. MgO, CaO, BaO and SrO), Gr. IIIa metal oxides (viz. Al(2)O(3), Ga(2)O(3), In(2)O(3) and Tl(2)O(3)), transition metal oxides (viz. TiO(2), Cr(2)O(3), MnO(2), Fe(2)O(3), CoO(x), NiO, CuO, ZnO, Y(2)O(3) and ZrO(2)), rare earth metal oxides (viz. La(2)O(3), Ce(2)O(3), Nd(2)O(3), Sm(2)O(3), Eu(2)O(3), Tb(2)O(3), Er(2)O(3) and Yb(2)O(3)) and U(3)O(8) [all prepared by depositing gold on corresponding metal oxide support by deposition precipitation (DP) and/or homogeneous deposition precipitation (HDP) method] were evaluated for their catalytic performance in the liquid phase epoxidation of styrene by tert-butyl hydroperoxide (TBHP) to styrene oxide and also in the solvent-free benzyl alcohol-to-benzaldehyde oxidation (by molecular oxygen or TBHP) reactions. For the epoxidation, the catalytic performance (styrene oxide yield) of the most promising nano-gold catalysts prepared by the HDP method was in the following order: Au/MgO > Au/Tl(2)O(3) > Au/Yb(2)O(3) > Au/Tb(2)O(3) > Au/CaO (or TiO(2)). However, for the oxidation of benzyl alcohol to benzaldehyde by molecular oxygen, the order of choice for the most promising catalysts (based on benzaldehyde yield) was Au/U(3)O(8) > Au/Al(2)O(3) > Au/ZrO(2) > Au/MgO. Whereas, when TBHP was used as an oxidizing agent for the benzyl alcohol oxidation, the order of choice for the most promising catalysts was Au/U(3)O(8) > Au/MgO > Au/TiO(2) > Au/ZrO(2) > Au/Al(2)O(3). The catalytic performance of a particular supported nano-gold catalyst was thus found to depend on the reaction catalysed by them. Moreover, it is strongly influenced by a number of catalyst parameters, such as the metal oxide support, the method of gold depositon on the support, the gold loading and also on the catalyst calcination temperature. Nano-gold particles-support interactions seem to play an important role in controlling the deposition of gold ( amount of gold deposited and size and morphology of gold particles), formation of different surface gold species (Au(0), Au(1+) and Au(3+)) and electronic properties of gold particles and, consequently, control the catalytic performance (both the activity and selectivity) of the supported nano-gold catalysts in the reactions. The nano-gold catalysts prepared by the HDP method showed much better catalytic performance than those prepared by the DP, coprecipitation or impregnation method; in general, the HDP method provided supported gold catalysts with much higher gold loading and/or smaller size gold particles than that achieved by the DP and other methods.
Keywords: Benzaldehyde; Benzyl alcohol; epoxidation; Metal oxide supports; Nano-gold catalysts; Oxidation; styrene; Styrene oxide

Epoxidation of styrene by t-butyl hydroperoxide over gold nanoparticles supported on Yb2O3: effect of gold deposition method, gold loading, and calcination temperature of the catalyst on its surface properties and catalytic performance - Choudhary, Vasant R.; Dumbre, Deepa K.; Patil, N. S.; Uphade, B. S.; Bhargava, Suresh Kumar (Journal of Catalysis, 2013)
Surface properties and epoxidation performance of Au/Yb2O3 catalyst are influenced by the method of gold deposition [viz. deposition-precipitation (DP), homogeneous deposition-precipitation (HDP) or impregnation], gold loading (0.9-6.6 wt%), and the catalyst calcination temperature (400-900 degrees C)]. The catalyst showed the best epoxidation performance when it was prepared by the HDP method and calcined at 500 degrees C. The Au/Yb2O3 catalyst even after calcination at 900 degrees C showed good activity and epoxide selectivity. Both Au-0 and Au3+ surface species were found in the catalyst calcined at 800 degrees C, but only Au-0 species were observed at the lower calcination temperatures (<600 degrees C). The selectivity for styrene oxide increased continuously with the reaction temperature (from 75 degrees C to 97 degrees C) and time (1-5 h), indicating that styrene oxide did not undergo secondary reactions under these conditions. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Au/Yb2O3 catalyst; Epoxidation of styrene; gold nanoparticles; Styrene oxide; tert-Butyl hydroperoxide

Calcium oxide supported gold nanoparticles as catalysts for the selective epoxidation of styrene by t-butyl hydroperoxide - Dumbre, Deepa K.; Choudhary, Vasant R.; Patil, Nilesh S.; Uphade, Balu S.; Bhargava, Suresh Kumar (Journal of Colloid and Interface Science, 2014)
Gold nanoparticles are deposited on basic CaO supports as catalysts for the selective conversion of styrene into styrene oxide. Synthetic methods, gold loading and calcination temperatures are varied to permit an understanding of their influence on gold nanoparticle size, the presence of cationic gold species and the nature of interaction between the gold nanoparticles and the CaO support. Based on these studies, optimal conditions are designed to make the Au/CaO catalyst efficient for the selective epoxidation of styrene. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Au/CaO; Epoxidation of styrene; gold nanoparticles; Homogenous deposition precipitation method; Styrene oxide